Grasslands in ‘Old World’ and ‘New World’ Mediterranean climate zones: past trends, current status and future research priorities Grass and Forage Science - Porqueddu, Claudio; Ates, Serkan; Louhaichi, Mounir; Kyriazopoulos, Apostolos; Moreno, Gerardo; Pozo, Alejandro del; Ovalle, Carlos; Ewing, Mike; Nichols, Phillip G. (Wiley, 2016)
Despite their ecological, economic and social importance, grasslands in areas with Mediterranean climates continue to receive limited scientific, political and media attention. The main objectives of this review are to compare and contrast dryland grasslands in the ‘Old World’ regions of the Mediterranean basin (southern Europe, western Asia and North Africa) with those of ‘New World’ regions with Mediterranean climates (Australia and Chile) and to identify common research priorities. The common characteristics and differences in climate, soils, native vegetation, importance of the livestock sector and the socio-economic background for the different Mediterranean environments are examined. Past trends and the current status of temporary and permanent Mediterranean grasslands are also described. Some common issues between these regions are as follows: (i) adaptation to climate change; (ii) increasing persistence and drought survival of both annual and perennial species; (iii) the important role of forage legumes; (iv) maintaining grassland plant diversity; and (v) improved ecosystem services, such as carbon sequestration, control of soil erosion and wildfires, and preservation of both wild and domestic biodiversity. The favourable climate in these regions, which allows year-round grazing and the growth of legumes, should be exploited to improve the sustainability of grassland-based, extensive farming systems and the quality of their animal products, while at the same time improving ecosystem services. The decreasing support for grassland research and development programmes requires increased international scientific and technical cooperation among the few institutions operating in the different Mediterranean-climate areas of the World to provide innovative and sustainable solutions to farmers.